Digital Correspondence in Business English: An Analysis of Students’ Email Writing in the AI Era - nur hasanah; Aisyah Mutiara Sani; Sri Wardani; Restina Liza; Muhammad Hasyimsyah Batubara (Yayasan Al-Afif, 2026)
The rapid advancement of artificial intelligence (Al) has had a significant impact on how students approach academic writing, particularly business correspondence. The purpose of this study is to examine students ability to write business emails in English, as well as the role of Altools like ChatGPT in shaping their writing practices. This study used a qualitative descriptive approach and included 20 English Education Department students. Data were gathered through semi-structured interviews and document analysis of students' email assignments. According to the findings, while most students can follow the basic structure. of business emails, they struggle with grammar accuracy, vocabulary use, clarity, and maintaining an appropriate level of formality. Artificial intelligence tools have been shown to improve writing quality, specifically grammar and sentence structure. However, the study discovered that students rely too heavily on Al, which may reduce their critical thinking and originality. Furthermore, students show varying levels of awareness regarding politeness and professional tone in email correspondence. This study emphasizes the importance of using Al as a supportive tool while also encouraging students to develop independent. writing skills.